1996
DOI: 10.1152/ajpendo.1996.271.3.e556
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of beta-adrenergic receptor-stimulated lipolysis in the heart by prostaglandins

Abstract: The purpose of the present study was to investigate the contribution of prostaglandins to lipolysis elicited by beta-adrenergic receptor activation in the heart. We have studied the effect of prostaglandin E2 (PGE2), prostaglandin I2 (PGI2), and their precursor arachidonic acid (AA) in the presence and absence of a cyclooxygenase inhibitor, sodium meclofenamate, on glycerol output elicited by stimulation of beta-adrenergic receptors in the isolated rabbit heart with isoproterenol (ISOP). Bolus injections of IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These agonists are stimulus for phospholipase A 2 and phospholipase C, both of which may provide a source of free arachidonic acid, an essential step in the generation of eicosanoids. It was also reported that badrenergic agonists stimulate arachidonic acid release in mammalian heart [8], but the mechanism by which arachidonic acid is released is not well documented.…”
mentioning
confidence: 99%
“…These agonists are stimulus for phospholipase A 2 and phospholipase C, both of which may provide a source of free arachidonic acid, an essential step in the generation of eicosanoids. It was also reported that badrenergic agonists stimulate arachidonic acid release in mammalian heart [8], but the mechanism by which arachidonic acid is released is not well documented.…”
mentioning
confidence: 99%